The Relationship Between Interest in Reading Maternal and Child Health Books and ANC Visits in Pregnant Women at Remote Areas of the Panaan Community Health Center - Nofina Estu Diajeng; Raden Maria Veronika Widiatrilupi (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2026)
Regular Antenatal Care (ANC) visits are crucial for maintaining maternal and fetal health, but in remote areas, access to health information is often limited. The Maternal and Child Health Handbook is an alternative educational medium, though its effectiveness depends on pregnant women’s interest in reading the book. This study aimed to identify the relationship between interest in reading the Maternal and Child Health Handbook and the regularity of ANC visits among pregnant women in remote areas of the Panaan Community Health Center (UPT). The study used an analytical observational design with a cross-sectional approach. A purposive sampling technique selected 30 pregnant women as respondents. Data were collected using a structured questionnaire covering respondent characteristics, knowledge of pregnancy health, interest in reading the handbook, and ANC visit data. Univariate and bivariate analyses were performed, with the Chi-Square test used for the latter. The results showed that 53.3% of respondents had a positive interest in reading the handbook, and 60% made regular ANC visits. Bivariate analysis revealed a significant relationship between reading interest and ANC visit regularity (χ²=10.24; p=0.001). Of the 16 women interested in reading, 87.5% made regular ANC visits, compared to only 28.6% of those without interest. In conclusion, pregnant women with higher interest in reading the Maternal and Child Health Handbook are more likely to make regular ANC visits, highlighting the need for efforts to increase reading interest through education and support.